Thermal insulation produced from rice husk agglomerated using starch produced by saccharomyces cerevisiae (2014)
Rice husk was agglomerated using different starch in order to obtain a required physical stability, with no effect in the thermal insulation properties. A process was developed using Saccharomyces Cerevisiae to produce the interior cavities in the agglomerate. The material was subjected to heating, loading, and to the ASTM C 177 test to evaluate the thermal conductivity. The tests showed that the material supports direct fire without producing any flame, it has an ultimate strength of 80 – 120 kPa when tested at temperatures ranging between 150 – 200 C. The thermal conductivity was found close to 0.09 W/m.K. At outdoor conditions (Dry bulb temperature: 30°C ± 5°C, Relative humidity: 80% ± 15%) the material was not attacked by natural fungus. The material can be recycled easily by nature, dissolving in the presence of water. These properties showed that the rice husk base agglomerated is an efficient thermal insulation, with an acceptable physical and chemical stability, suitable for engineering applications and environmental friendly.